Corrosion behavior of AISI 1020 steel in MEA and [Bmim]BF4 mixed solution containing saturated CO2. (March 2020) - He, San; Qiu, Yunpeng; Sun, Yinjuan; Zhang, Zhihao; Cheng, Jie; Gao, Chaoyang; Zhao, Zhichao
Highlights: The corrosion behavior of AISI 1020 steel in MEA solution mixed with ionic liquid ([Bmim]BF4 ) was investigated. [Bmim]BF4 has an inhibition effect of uniform corrosion, but it can cause pitting corrosion. The existence of F − is the main cause of pitting corrosion. Abstract: Recently, the excellent performance of ionic liquid and MEA mixed solution as CO2 absorbent has been researched by many scholars, while the corrosion mechanism of the mixed solutions is less discussed. In this work, the corrosion behavior of AISI 1020 steel in MEA and [Bmim]BF4 mixed solutions Containing saturated CO2 was studied by weight loss experiment. Morphology of scales and metal surface was studied by SEM and EDS. The surface state of the electrode was analyzed by electrochemical impedance spectroscopy (EIS) fitting equivalent circuit, and Passivation law of the passivation zone was analyzed by potentiodynamic scanning test. The results show that in the mixed solution saturated with CO2, MEA will degrade and increase the uniform corrosion rate of AISI 1020 steel. When [Bmim]BF4 is added to MEA solution, the uniform corrosion rate is inhibited; however, due to the dissociation of F − in BF4 -, as the concentration of [Bmim]BF4 increases, the range of passivation region becomes narrower, and the stability of the passivation film becomes worse, which induces pitting corrosion of AISI 1020 steel.